The Learning of Arabic Alphabets for Special Needs Students in Elementary School - Irma Rachmayanti; Mochamad Arifin Alatas (Arabic Education Department, Islamic Studies Faculty, Universitas Muhammadiyah Malang, 2020)
This research was motivated by the learning of Arabic letters in students with special needs as a basic stage of learning Arabic and the Qur’an. This study aimed to describe the learning of Arabic letters in students with special needs in elementary school Campurdarat Tulungagung East Java Indonesia.This type of research was descriptive qualitative. Data collection techniques by interview, observation, and documentation. Sources of data in this study were principals, teachers, students with special needs, and documents. The results of this study were descriptions of the learning of Arabic letters for students with special needs in elementary schools. (1) Learning planning included promissory notes, syllabus, and lesson plans like schools in general. (2) The implementation of learning included teaching materials with Islamic handbooks while learning methods included alphabetical methods, demonstrations, recitation, and lectures dominated by sign language, while the learning media included cards and Juz ‘Amma. (3) Evaluation of learning included evaluation of processes and results that show students with special abilities can identify Arabic letters, but difficulties in pronunciation.